Are Advances in Survival Among the Oldest Old Seen Across the Spectrum of Health and Functioning?. (13th January 2020) - Thinggaard, Mikael; Jeune, Bernard; Osler, Merete; Vaupel, James W; McGue, Matt; Christensen, Kaare
Abstract: Background: Mortality rates have been reduced by half over the last 60 years for nonagenarians, and the progress is continuing. The greater survival might be due to overtreatment of severely physically and cognitively disabled individuals, which is a big concern for societies and individuals. Methods: The study population comprised two Danish birth cohorts: the 1905 Cohort and the 1915 Cohort. At age 95, all from the two cohorts who were still alive and living in Denmark were invited to participate in a health survey that used the same assessment instrument. A total of 2, 670 (56.8%) persons participated in the two surveys and survival was assessed through a 7.3-year follow-up period during which 2, 497 (93.5%) had died, and with virtually no loss to follow-up. Results: Despite the increasing chance of surviving to age 95, the 1915 Cohort had significantly better health and functioning than the 1905 Cohort. The survival advantage in the 1915 Cohort continued in the follow-up period after age 95: Median survival length was 2.4 months longer, p = .011. This advantage was not statistically associated with different levels of activities of daily living, physical performance, cognitive functioning, self-rated health and life satisfaction. However, the advantage tended to be more pronounced among people with better health. Conclusions: Life span and health increases among the oldest old. The improvement in survival for 95-year olds born in 1915 compared with 1905 was seen across the whole spectrum of health and functioning, with a tendency towards bigger improvement among those in good health.